The Adinatha Temple in the Bhandasar Temple Complex - Temples of India Project (Jio Institute, 2024)
The Adinatha or Rishabnatha Temple in the Bhandasar Temple Complex. It is a subsidiary shrine situated to the south of the complex. It is relatively smaller in size than the Bhandasar Temple. The temple is not austere in treatment. It is a simple structure with planned walls and one entrance facing the east.